Innovations in travel demand modeling summary of a conference [held] May 21-23, 2006, Austin, Texas. Volume 2, - Turnbull, Katherine F. (Transportation Research Board, 2008)
On May 21 through 23, 2006, the Transportation Research Board (TRB) convened the Innovations in Travel Demand Modeling Conference in Austin, Texas. The conference was sponsored by the following agencies, organizations, and companies to provide an opportunity for a frank exchange of ideas and experiences among academics, model developers, and practitioners: TRB, FHWA, FTA, the Central Texas Regional Mobility Authority, the Capital Metropolitan Transportation Authority, PBS & J-Austin, URS Corporation, and HNTB Corporation. Approximately 220 individuals from across the transportation research community at national, state, regional, and local levels and from the public and private sectors and academia participated. The last major conference on specialty travel demand modeling was held as part of the U.S. Department of Transportation's Travel Model Improvement Program (TMIP) in the fall of 1996. At that time, there was little research and no practical application of land use models and activity-based travel demand models and their integration with demographic, economic, and network modes. Since then, there has been a literal revolution in travel demand forecasting.
Title from PDF title screen.
Keywords: Choice of transportation -- Mathematical models -- Congresses.; Transportation demand management -- Congresses.; Travel -- Mathematical models -- Congresses.; elektronické knihy; electronic books